Orthotic treatment of hip dislocation derived from femoral neck osteomyelitis. Two cases report - José Julio Requeiro Molina; Ana María Machado Consuegra; Liyanira Alonso Leiva; Juana María Morejón Fernández; Gabriela María Requeiro Molina; José Julio Requeiro Morejón (Medisur)
Osteomyelitis is a bone inflammation caused mainly by bacteria. In cases of the femur’s neck osteomyelitis and concomitant septic arthritis, complications can lead to considerable joint shortening and deterioration in the long term. The cases of two neonatal patients are described, with hyperthermia manifestations as a common sign; and only in one of them limited movement of the right lower limb, flexion and adduction contracture, painful on movement. The diagnosis was based on clinical, imaging and laboratory criteria. The treatment consisted in the use of the abduction splint, which guaranteed the concentric reduction of the femoral head in the acetabular cavity; this could be verified by monitoring and control of the reduction, through simple radiography of the pelvis in each consultation. The early diagnosis of the disease determines the use of a more conservative treatment, in addition to minimizing complications.